Terahertz spin-selective metasurface for multichannel switching of OAM - Kaiyu Guo; Miao Zhang; Zhiqiang Du; Zhengyong Song (Results in Physics, 2024)
Thanks to switchable wavefronts, design methods of diverse functions are greatly enriched. However, less attention has been paid to multichannel switchable orbital angular momentums (OAMs) of metasurfaces in previous reports. In this work, a spin-selective metasurface enabling multichannel switchable OAMs is proposed in terahertz band. This metasurface is designed based on the phase change property of vanadium dioxide (VO2). Firstly, when VO2 is metal, vortex beam with topological charge of l = 2 is achieved under left-handed circular polarization (LCP) incidence. Under right-handed circular polarization (RCP) incidence, the obtained vortex beam has a topological charge of l = -3. Secondly, when VO2 is changed to insulator, function of the metasurface is correspondingly switched. Under LCP and RCP incidences, vortex beams are realized with topological charges of l = 3 and l = -2. Therefore, the designed metasurface as a multichannel vortex beam generator has switchable characteristic. Our design shows great promise in the integration of multifunctional devices.